Factors influencing rice farmers to participate in agricultural development programme - Madlaim, Nur Izatul Nadhirah; Kamarul Zaman, Nur Badriyah (International Journal of Accounting, Finance and Business, 2025)
Rice is a strategic commodity for Malaysia as it is the staple food for Malaysians. However, the rice sector constantly faces various challenges that lead to unsustainable supply, directly threatening food security in the country. Therefore, the rice sector always receives government intervention such as organizing expansion programs aimed at increasing rice yields in the country. Although the policy of rice sufficiency through local production has long been the main focus of the government, however, to make these policies successful, the participation from the target group, namely the rice farmers, is the main determinant of the success of a program. The question is, what are the probability factors that influence rice farmers to accept or participate in the development programs to increase rice yields that have been organized by the extension agencies. Therefore this study seeks to understand the factors that influence farmers to participate in agricultural development programs organized by extension agencies. A systematic literature review of the peer-reviewed literature was undertaken to analyze the related factors that influenced farmers to participate in agriculture development programs.